STRATEGI PENGELOLAAN DANA WAKAF TUNAI DI INDONESIA: SEBUAH PENDEKATAN METODE AHP - Aam S. Rusydiana; Abrista Devi (Universitas Siliwangi, 2019)
Waqf is one of Islamic law that concern to people’s lives which is has a function for the community interest in order to obey to Allah SWT. In practice, waqf in Indonesia faces many hard problems, because commonly known as non-productive waqf. Talking about cash waqf, waqf institution not only as religious rituality but also could touch humanity aspect by empowering its potency to maximize public wealth. This research is aim to identify the priority factors that being barrier to develop the practice of cash waqf in Indonesia using AnalyticHierarchy Process (AHP) method. Here is also offered some solutions for the problems identified. Result show that the problems appeared in managing cash waqf in Indonesia divided into 4 important aspects, there are: Human Resource aspect, trust aspect, system aspect, and sharia aspect. The rank for most priority problems to less priority based on the priority result are: 1) trust problems (whereas the most priority for this sub-criteria is donators’ lack of trust), 2) sharia problems (is unfulfilled waqf covenants), 3) human resource problems (is misappropriation of waqf funds, 4) system problems (is weak of management systems). Strategies that can be built to develop the practice of cash waqf in Indonesia based on the priorities are: 1) the development of waqf education institutions, 2) more computerized cash waqf management, 3) more comprehensive fund manager quality improvement, 4) transparency and accountability in every step. The overall results are relatively consistent with studies Rusydiana and Devi (2013) on the same theme, although there is little difference in terms of eigenvalue